Asset Bubbles without Dividends - An Experiment - Jörg Oechssler; Carsten Schmidt; Wendelin Schnedler (University of Heidelberg, Department of Economics, 2009)
Bubbles in asset markets have been documented in numerous experimental studies. However, all experiments in which bubbles occur pay dividends after each trading day. In this paper we study whether bubbles can occur in markets without dividends. We investigate the role of two features that are present in real markets. (1) The mere possibility that some traders may have inside information, and (2) the option to communicate with other traders. We find that bubbles can indeed occur without dividends. Surprisingly, communication turns out to be counterproductive for bubble formation, whereas the possibility of inside information is, as expected, crucial.
urn:nbn:de:bsz:16-opus-94687
Keywords: C92; G12; D8; 330; asset markets; bubbles; experiment; mirages; dividends; Finanzmarkt; Spekulationsblase; Dividende; Test; Theorie